Studi Kearifan Lokal Petani Lembang Tumbang Datu dalam Proses Usaha Tani Padi - Albertinhennyranteallo Albertinhennyranteallo; Yunus, Awaluddin; Bakri, Suardi (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Agricultural practices that take local wisdom into account can provide significant benefits to the environment and society. Local wisdom plays a crucial role in sustainable agricultural practices. Time-tested knowledge and practices can provide solutions to the challenges faced by modern farmers, particularly in the context of climate change and environmental degradation. However, despite extensive research, a significant research gap remains, specifically how local wisdom in the Tumbang Datu Valley can be integrated into broader agricultural policies. The research used was descriptive with a qualitative approach. Qualitative research aims to understand social phenomena from the perspective of participants. Initial informants were selected purposively, selecting informants deemed to have extensive knowledge of the conditions in the village under study, using a snowball sampling technique. The first step was to identify key informants, who in this study consisted of 16 traditional leaders and farmers familiar with the culture in Lembang Tumbang Datu and directly involved in the practice. The local wisdom in the rice farming process, from pre-planting, planting, maintenance, to harvesting and post-harvest, is implemented based on ancestral heritage in line with environmental conservation. Farmers demonstrate their concern for nature through natural soil cultivation, selection of superior seeds, use of organic fertilizers, and implementation of efficient planting and irrigation systems. The application of Integrated Pest Management (IPM) and post-harvest technology demonstrates the farmers' ability to adapt to innovation while maintaining local wisdom. Overall, the rice farming system in Lembang Tumbang Datu demonstrates the synergy between tradition and modernity, supporting food security while preserving cultural heritage.